Pemberdayaan Pengelola Buah Pala Berbasis Kualitas Produk untuk Keberlanjutan Usaha - Gemina, Dwi; Kartini, Tini; Haris, Helmi; Sudarijati, Sudarijati; Andari, Titiek Tjahja; Nurjanah, Dewi Astri (Universitas Pahlawan Tuanku Tambusai, 2026)
Community empowerment based on product quality as a form of community service. The method used is Focus Group Discussion (FGD) and a participatory approach is used in this activity through counseling using lectures, mentoring, instruction, question and answer, discussion, simulation and practice methods. Activities carried out include: transfer of financial management knowledge; transfer of packaging knowledge; various marketing models; transfer of quality and production capacity of nutmeg as well as providing motivation and utilizing business opportunities and financial management information. This community service program is a form of implementation of the Tri Dharma of Higher Education for Djuanda University with the work results of lecturers being used by the community.